Serum Concentrations of Osteocalcin (OC) and Beta-Cross Laps (Beta-CTx) and Insulin Resistance in Morbid Obese Women with and without DM2 - Arrieta F; Iglesias P; Piñera M; Arrieta A4; Quiñones J; Balsa J; Vazquez C (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2017)
Aim: The present study was intended to establish the role of bone in grade III obese women with and without type 2 diabetes mellitus (T2DM).  Material & Methods: Serum osteocalcin (OC), Beta Cross-Laps (Beta-CTx), parathormone (PTH) separar and y 25-hydroxyvitamin D (25OHD) concentrations were measured in 48 morbid obesity women (11 with T2DM and 37 control group). Insulin resistance and insulin secretion was assessed by measuring the HOMA-IR and the HOMAβ index and its association with OC and Beta-CTx.  Results: Serum OC was significant lower in the diabetic group compared with non-diabetic patients 15.4 ± 3.6 ng/ml vs 22.1 ± 3.5 ng/ml, p<0.001 without significant differences in Beta-CTx (0.24 ± 0.1 vs 0.31 ± 0.2 ng/ml, ns). Both bone biomarkers, OC and Beta-CTx, showed a positive correlation (r=0.76; p<0.01) in the whole group subjects and in the control group (r=0.80, p<0.00), but no in the T2DM group (r=0.50, p ns). In the whole group of patients, OC correlated significantly with HOMA-IR (r=0.36; p<0.01) and HOMA-ß (r=0.36, p<0.01). Beta-CTx also correlated with HOMA-IR (r= 0.40, p<0.01) and HOMA-ß (r= 0.41, p<0.001. OC also significantly correlated with HOMA-IR (r=0.41, p<0.01) in non-diabetic patients and almost reached statistical significance with HOMA-ß (r=0.32, p=0.053), but was not significantly correlated with HOMA-ß (r= -0.53, ns) and with HOMA-IR index (r=0.52, ns) in the T2DM group. When we performed the multivariate logistic regression the serum level of OC was the only covariate found significantly with DM2 with a coeficient -6.65 , (95% CI, -12.75049 -.5674469 ); p = 0.03). Both groups showed secondary hyperparathyroidism (T2DM, 78.4 ± 19.4 pg/ml vs non-diabetic group, 75.4 ± 35.6 pg/ml; ns). The majority of the patients showed 25OHD deficiency 62.5%, followed by 25OHD insufficiency 27.1% and normal 25OHD levels in only 10.4%. The 25OHD deficiency was present in both study groups (T2DM patients, 18.3 ± 7.4 pg/ml and nondiabetic group, 19.7 ± 9.6 pg/ml; ns). Conclusion: OC and Beta-CTx could play a role in glucose metabolism and insulin resistance. Serum OC concentrations are significantly reduced in T2DM morbidily obese women compared with non-diabetic group, and add new evidence on the possible role of bone as an endocrine organ with metabolic implications specially the levels of OC.